Penerapan Model Pembelajaran Kooperatif Tipe NHT dan Pengaruhnya pada Pembelajaran Tematik Terpadu di Sekolah Dasar - Maissy Yuliany; Zuardi Zuardi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
The purpose of this reseacrh was to effect of Cooperative Learning Type Numbered Head Together on student learning outcomes in Integrated Thematic Learning  in Class V SDN 01 Matur even semester of academic year 2018/2019. This research is a quantitative research with type experimental research, and quasy experimental research design. Sampling data was collected with purposive sample technique. The sample of this study amounted to 40 people with population 40 people. Instrument that used to collecting  data in this research is objevtive test with multiple choice form. The result of research is that tcount > ttable is 2,7 > 1,72 with α = 0,05 meaning H0 is rejected. The average of student learning measured with posttest after done learning, that is in experiment class 80,6 and control, class 76,2. So that Ha accepted that there is effect the use of model Cooperative Type Numbered Head Together on student learning outcomes in integrated thematic leraning in class V SDN 01 Matur Kabupaten Agam